2014
DOI: 10.1016/j.jebo.2014.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation in local and global groups

Abstract: -Multiple group memberships are the rule rather than the exception. Locally operating groups frequently offer the advantage of providing social recognition and higher marginal benefits to the individual, whereas globally operating groups may be more beneficial from a social perspective. Within a voluntary contribution environment we experimentally investigate the tension that arises when subjects belong to a smaller local and a larger global group. When the global public good is more efficient individuals firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 21 publications
2
40
0
Order By: Relevance
“…Moreover, in our xed-matching condition we nd no signi cant increase in allocations to the global account in treatment FH compared to FL. On the other hand, allocations to the global public good increase signi cantly in the corresponding rematched-groups treatments (Result 3), which is consistent with previous research on the MLPG game using milder forms of group identity (Blackwell and McKee, 2003;Fellner and Lünser, 2008). Taken together, these results indicate that the ndings of the previous studies may not be robust to the form of the group identity manipulation.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Moreover, in our xed-matching condition we nd no signi cant increase in allocations to the global account in treatment FH compared to FL. On the other hand, allocations to the global public good increase signi cantly in the corresponding rematched-groups treatments (Result 3), which is consistent with previous research on the MLPG game using milder forms of group identity (Blackwell and McKee, 2003;Fellner and Lünser, 2008). Taken together, these results indicate that the ndings of the previous studies may not be robust to the form of the group identity manipulation.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies of the MLPG game typically nd that contributions to the global public good are increasing in the relative return on the global account compared to the local one (Blackwell and McKee, 2003;Fellner and Lünser, 2008;Chakravarty and Fonseca, 2013). However, since the Tullock contest potentially induces a much stronger form of in-and out-group identity than has previously been considered in this literature, this…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…7 Note that coordination could also be affected by binding budgets, as experimentally highlighted by Seely et al (2005). 8 See also Fellner and Lünser (2008) and Falk et al (2013) for related experimental findings. 9 The authors compare results from a benchmark linear public good game with those observed in a setting with two identical linear public goods associated with the same marginal per capita return used in the benchmark.…”
Section: Literature Reviewmentioning
confidence: 97%
“…By design our setup is related to a small body of literature on public goods provision that involves multiple layers of independent contribution decisions (see, e.g., Blackwell and McKee, 2003;Fellner and Lünser, 2014). A key feature that differentiates our study from theirs is that decision makers in multi-level public goods games need to trade off contributions between a local and a global level public good.…”
Section: Introductionmentioning
confidence: 99%